Igor Stravinsky: The Rite of Spring—phenomenological research on six piano students engaged in interdisciplinary project-based learning - Pucihar, Ilonka (Frontiers in Education, 2025)
BackgroundThe main aim of this research was to explore the experiences, understanding and interpretation of interdisciplinary, project-based learning (PBL) in the context of studying Stravinsky’s The Rite of Spring, with a specific focus on his own arrangement for piano duet (four hands). Specifically, the study sought to qualitatively examine how student pianists perceive and make sense of participating in such an educational approach. Understanding these perspectives can contribute to the broader discussion of innovative teaching methods in music education.MethodsThe study involved six master’s degree students at the Academy of Music, University of Ljubljana. Data were collected through multiple qualitative methods, including research diary, transcripts of phenomenological interviews, and reflective evaluation diaries maintained by the students. The data were analyzed using interpretative phenomenological analysis, which helped identify key themes related to the students’ experiences with interdisciplinary PBL.ResultsThe analysis of the data revealed four main themes: the search for artistic freedom, reduction of performance anxiety, positive group dynamics, and reflections on artistic and pedagogical development. The students stated that engaging with Stravinsky’s revolutionary work inspired a desire to explore their own artistic creation beyond traditional norms. The interdisciplinary PBL approach helped reduce performance anxiety by fostering greater involvement with the story and emphasizing collective rather than individual performance. Additionally, positive group dynamics—marked by shared goals, safety, collaboration, and connectedness—were central to their experience. Finally, participating in this approach broadened the students’ perspectives on their future development, instilling confidence to pursue new creative and pedagogical directions.DiscussionThe findings suggest that interdisciplinary PBL can serve as a powerful pedagogical tool in music education, fostering artistic freedom, reducing anxiety, and promoting collaborative skills. The positive group dynamics and expanded development perspectives that emerged indicate that such approaches can enhance both personal growth and professional readiness among students. Overall, this study contributes valuable insights with regard to the impact of interdisciplinary PBL on student learning and development in the context of advanced musical education.